2021
DOI: 10.3390/catal11101225
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Suitability of Engelhard Titanium Silicate as a Support for Ni-Catalysts in the Methanation Reaction

Abstract: Methanation reaction of carbon dioxide is currently envisaged as a facile solution for the storage and transportation of low-grade energies, contributing at the same time to the mitigation of CO2 emissions. In this work, a nickel catalyst impregnated onto a new support, Engelhard Titanium Silicates (ETS), is proposed, and its catalytic performance was tested toward the CO2 methanation reaction. Two types of ETS material were investigated, ETS-4 and ETS-10, that differ from each other in the titanium content, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…[197,198] Corma et al used ML methods to predict synthesis conditions for successful zeolite syntheses, [199] a wellknown greenhouse gas adsorbent. [200,201] They elucidated the relationships between different synthesis parameters with the performance of Ti-silicates using a NN model, and used this to optimize the synthesis of the next generation of materials using a genetic algorithm. Specifically, they found that the catalytic performance of the zeolite was enhanced by decreasing the amount of organic modifier while maintaining the OH/Si ratio of ≈0.2.…”
Section: Zeolitesmentioning
confidence: 99%
“…[197,198] Corma et al used ML methods to predict synthesis conditions for successful zeolite syntheses, [199] a wellknown greenhouse gas adsorbent. [200,201] They elucidated the relationships between different synthesis parameters with the performance of Ti-silicates using a NN model, and used this to optimize the synthesis of the next generation of materials using a genetic algorithm. Specifically, they found that the catalytic performance of the zeolite was enhanced by decreasing the amount of organic modifier while maintaining the OH/Si ratio of ≈0.2.…”
Section: Zeolitesmentioning
confidence: 99%